Hematological and biochemical parameters in Spotted Paca (Cuniculus paca) undergoing pharmacological restraint and general anesthesia - Uscategui, R. A. R. [UNESP] (2019)
The aim of this study was to assess the effects of chemical restraint, general anesthesia and opioid treatment on hematological components in Cuniculus paca. Eight healthy, adult, captivity female animals, underwent three laparoscopic procedures with a 15-day interval were evaluated. After physical restraint, an association of ketamine (25mg/kg) and midazolam (0.5mg/kg) was administered intramuscularly for chemical restraint. Posteriorly, anesthesia was induced and maintained with isoflurane; and randomly administered methadone (0.5mg/kg), tramadol (5mg/kg) or saline-placebo (0,1mL/kg) intramuscularly. After pharmacological restraint and in the final laparoscopy stage, venous blood samples were obtained for complete blood count, total plasma protein (TP), creatinine, alanine aminotransferase (ALT), sodium, potassium, chloride and ionized calcium analysis. During general anesthesia, hemoglobin, TP concentration and lymphocytes decreased (P=0.029; <0.001; 0.022 respectively), whereas the potassium levels increased (P=0.034). In conclusion, chemical restraint with ketamine/midazolam association causes a slight decrease in blood cellular components. Isoflurane anesthesia for laparoscopic procedure lead to decrease in hemoglobin, lymphocytes and protein concentrations, while potassium increased, without any influence from the tramadol or methadone treatment. However, these alterations were transient, and its hematologic values can collaborate in carrying out epidemiological, pathophysiological or case studies in the Cuniculus paca.